Caracterização e aplicação da Blenda PEDOT : PSS/PVA na construção de eletrodos transparentes e dispositivos eletroluminescentes - Carr, Olivia [UNESP] (2015)
Since the discovery of the electronic properties of synthetic organic polymeric materials, several studies have been made to develop electronic and opto-electronics devices such as field effect transistors, light emitting diodes, light emitting electrochemical cells, solar cells and sensors. The motivation for this research was some specific features of organic materials such as flexibility, ultra-thin thickness, low cost and easy processing for application as transparent electrode in organic devices. This work aimed to study and characterize the polymer blend formed by the conductive polymer poly (3,4-ethylenedioxythiophene): poly (estirenosulfonado) (PEDOT:PSS) and the insulating polymer poly (vinyl alcohol) (PVA). The samples were characterized by spectroscopic techniques (UV-Vis), morphological (AFM) and electrical measurements AC and DC. The blend (PEDOT:PSS/PVA) containing (40/60), respectively, resulted in a percolated material, wherein the conductivity increases linearly with the concentration of conductive polymer. The results showed that the charge transport in the blends can be well described by the Variable Range Hopping (VRH-3D) model. Samples with concentrations below 10% by weight of PEDOT:PSS in the blend showed phase separation of the constituent polymers, resulting in two distinct electrical conduction processes, a predominant via the insulating matrix (PVA) and a second via islands formed by the polymer conductor (PEDOT:PSS). Optical characterization of the blend, for applications as transparent electrode, reveals that high electrical conductivity and low coefficient of optical absorption is obtained for concentrations close to 30% of PEDOT:PSS. The composition of the blend (PEDOT:PSS/PVA) with micro particles of Zn2SiO4:Mn, results in light emitting devices with emission peak at 530 nm and color purity of 88%